Heart Rate Variability and Heart Failure with Reduced Ejection Fraction: A Systematic Review of Literature - Nagai, Michiaki; Ewbank, Hallum; Nakano, Yukiko; Scherlag, Benjamin J.; Po, Sunny S.; Dasari, Tarun W. (Current Cardiology Reviews, 2025)
IntroductionAutonomic impairment is a hallmark of heart failure with reduced ejection fraction (HFrEF). While there have been studies on general values for each index of heart rate variability (HRV) analysis in HFrEF, a systematic review comprehensively examining representative values in HFrEF is lacking.MethodsWe searched PubMed, Embase, and Cochrane databases to extract studies reporting representative values of HRV metrics in HFrEF.ResultsA total of 470 HFrEF patients from 6 studies were included in the review. In general, time and frequency domains were abnormally lower in HFrEF, portending a worse prognosis. In HFrEF, the mean or median value of the standard deviation of NN interval, root mean square successive difference, pNN50, and low-frequency power/high-frequency power were 40 to 121 msec, 19 to 62 msec, 1.3 to 14%, and 1.00 to 1.73, respectively.ConclusionIn this systematic review, most HRV metrics were found to be calculated from 24-hour Holter recordings and were lower in HFrEF patients with poor prognosis.
Keywords: Heart rate variability